Large‐Area All‐Printed Temperature Sensing Surfaces Using Novel Composite Thermistor Materials. (3rd December 2018) - Katerinopoulou, Dimitra; Zalar, Peter; Sweelssen, Jorgen; Kiriakidis, George; Rentrop, Corné; Groen, Pim; Gelinck, Gerwin H.; van den Brand, Jeroen; Smits, Edsger C. P.
Abstract: Surfaces which can accurately distinguish spatial and temporal changes in temperature are critical for not only flow sensors, microbolometers, process control, but also future applications like electronic skins and soft robotics. Realizing such surfaces requires the deposition of thousands of thermal sensors over large areas, a task ideally suited for printing technologies. Negative temperature coefficient (NTC) ceramics represent the industry standard in temperature sensing due to their high thermal coefficient and excellent stability. A drawback is their complex and high temperature fabrication process and high stiffness, prohibiting their monolithic integration in large area or flexible applications. As a remedy, a printable NTC composite that combines a rapid and scalable all‐printed fabrication process with performances that are on par with conventional NTC ceramics is demonstrated. The composite consists of micrometer‐sized manganese spinel oxide particles dispersed in a benzocyclobutene matrix. The sensor has a B coefficient of 3500 K, with a 4.0% change in resistance at 25 °C, comparable to bulk ceramics. The selected polymer binder yields a composite exhibiting less than a 1 °C change in resistance to changes in humidity. The sensor's scalability is validated by demonstration of a A4‐sized temperature sensing sheet consisting of over 400 sensors. Abstract : Temperature sensing over large areas is enabled by the development of a screen‐printable negative temperature coefficient ceramic composite. The developed sensor has electrical characteristics that are comparable to a bulk ceramic component with excellent stability in changing humidity. Implementation was demonstrated in a sensor sheet capable of distinguishing temperature of less than 0.1 °C across its surface.